Coronavirus 2′-O-methyltransferase: A promising therapeutic target - Craig Schindewolf; Vineet D. Menachery (Virus Research, 2023)
Coronaviruses (CoVs) have been the source of multiple epidemics and a global pandemic since the start of century, and there is an urgent need to understand CoV biology and develop better therapeutics. Here, we review the role of NSP16 in CoV replication, specifically its importance to 2′-O-methylation and CoV RNA capping. We describe the attenuation phenotypes of NSP16-mutant CoVs, the roles of MDA5 and IFITs in sensing and antagonizing viral RNA lacking 2′O methylation, and the dependence on 2′-O-methylation in other virus families. We also detail the growing body of research into targeting 2′-O-methylation for therapeutics or as a platform for live attenuated vaccines. Beyond its role in RNA capping, NSP16 may have yet uncharacterized importance to CoV replication, highlighting the need for continued studies into NSP16 functions. Understanding the full contribution of NSP16 to the replicative fitness of CoVs will better inform the development of treatments against future CoV outbreaks.